2006
DOI: 10.1111/j.1365-2915.2006.00607.x
|View full text |Cite
|
Sign up to set email alerts
|

Revision of the Ketaketa subcomplex of blackflies of the Simulium damnosum complex

Abstract: A revision of the taxonomy of the Ketaketa subcomplex of the Simulium damnosum Theobald complex (Diptera: Simuliidae) is presented including new material from Tanzania, Malawi and South Africa. The cytotaxonomy, morphology and molecular identity of known and new taxa are described. The Ketaketa subcomplex is cytotaxonomically defined by the paracentric inversion 1L-7. We recognize three sibling species, namely Simulium latipollex (Enderlein), Simulium plumbeum Krueger, sp.n. and Simulium kipengere Krueger, sp.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 23 publications
(73 reference statements)
1
12
0
Order By: Relevance
“…[35]. The cytoforms present in Mahenge are ‘Nkusi’, Simulium plumbeum (= ‘Hammerkopi’ and ‘Ketaketa’), ‘Sebwe’ and ‘Turiani’ [35, 54, 55]. ‘Nkusi’ is thought to be the predominant anthropophilic species, and S .…”
Section: Methodsmentioning
confidence: 99%
“…[35]. The cytoforms present in Mahenge are ‘Nkusi’, Simulium plumbeum (= ‘Hammerkopi’ and ‘Ketaketa’), ‘Sebwe’ and ‘Turiani’ [35, 54, 55]. ‘Nkusi’ is thought to be the predominant anthropophilic species, and S .…”
Section: Methodsmentioning
confidence: 99%
“…The chromosome spreads were prepared as described by Krü ger (2003). The analysis of the chromosomal banding patterns was carried out using reference maps (Dunbar, 1969;Vajime and Dunbar, 1977;Procunier and Muro, 1993;Cupp, 1993, 1994;Krü ger et al, 2004Krü ger et al, , 2005Mustapha et al, 2004;Krü ger, 2005) and specimens representing the chromosomal standard (S. kilibanum, Uganda) or relatives [S. mengense from Cameroon, kindly provided by M. Mustapha, and S. pandanophilum from Uganda (Krü ger et al, 1998)]. …”
Section: Methodsmentioning
confidence: 99%
“…The analysis revealed that there were three geographical isolates [excluding the cytotype, described, as the 'Olifants' form within the 'Ketaketa' subcomplex, by Krü ger et al (2005)], all of which closely resemble the S. damnosum cytoform 'Nkusi', which is otherwise known only from East Africa. Characteristically, the three isolates, here named the 'Nkusi SA', 'Nkusi SW' and 'Pienaars' forms, all share the fixed inversion ] and standard sequences on the 1S, 1L, 2S and 3S chromosome arms.…”
Section: South Africa and Swazilandmentioning
confidence: 99%
See 1 more Smart Citation
“…Use of cytotaxonomy does permit some species to be recognized as members of a complex (Table 4), but can require a large number of specimens in order to yield interpretable material (Spironello et al 2002) depending upon environmental conditions; e.g., only 1 in 10 larvae could display a proper chromosome spread on a slide (Spironello et al 2002). Moreover, inappropriate larval storage at high temperature may lead to poor results, due to chromosome morphology alteration, and inexperienced staff could misidentify larvae; some chromosomal inversions have been misidentied in the subcomplex Ketaketa of Simulium damnosum Theobald (Krueger et al 2006). Furthermore, cytotaxonomy can only be applied to late larval instars (Xiong and Kocher 1991) and does not allow adult female black y identi cation, which is quite important for epidemiological studies (Krüger et al 2000).…”
Section: Limitations and Limits Of Larval Identitymentioning
confidence: 97%